Media representations of sexual violence by perpetrators with disabilities: a Sara Mills analysis - Bukran Habibullah; Anwar Efendi; Rahmat Rahmat; Silvia Al Viana (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
This study examines the representation of sexual violence involving a perpetrator with a physical disability (locomotor disability) in the online media portal Tribunnews.com. The case presents a unique discursive phenomenon where the perpetrator’s physical condition triggers a narrative contestation regarding crime and vulnerability. This study employed qualitative critical discourse analysis using Sara Mills’ framework. Data from seven news articles were analyzed through a three-stage procedure: identifying the subject position (agency and narrative control), examining the object position (passive representation), and interpreting the power relations implied within the textual structure. The results reveal an asymmetrical pattern of representation between the perpetrator and the victim. The perpetrator is consistently constructed as a dominant subject through discursive strategies that highlight emotional narratives and disability accommodations, which shifts the news focus from the criminal act to demands for public sympathy. Conversely, the female victim is marginalized as a passive object whose direct perspective is either filtered through third-party advocates or completely omitted from the narrative. This structural imbalance positions the perpetrator as the focal point of legal and social empathy while subordinating the victim's trauma.